P115 Escherichia coli Nissle 1917 modulate gut microbiota composition in ulcerative colitis patients. (26th January 2017) - Graziani, C.; Petito, V.; Del Chierico, F.; Mangiola, F.; Pecere, S.; Schiavoni, E.; Pizzoferrato, M.; Lopetuso, L.R.; Putignani, L.; Gasbarrini, A.; Scaldaferri, F.
Abstract: Background: Escherichia coli Nissle 1917 (ECN) is a Gram-negative bacteria that belongs to the family of Enterobacteriaceae, and it is currently used as probiotic drug in the management of infectious gastroenteritis and in maintenance of remission in ulcerative colitis (UC) patients. ECN has been described to act also on intestinal epithelial barrier but few information exists on the influence of this probiotic on the gut microbiota composition. Methods: The aim of our study was to evaluate the effect of administration of ECN in the qualitative and quantitative composition of the intestinal bacterial flora. Five patients affected by UC were treated with ECN (1 pill daily) for 10 days follwed by 2 pills per day for further 20 days. Fecal samples were collected before starting the treatment (T0), after 10 days from the beginning of the therapy (T1) and one month following the start of treatment (T2). Genomic DNA was isolated from fecal samples. The V1-V3 region of 16S rRNA locus was amplified on a 454-Junior Genome Sequencer. Reads were analyzed and grouped into operational taxonomic units (OTUs) by sequence matching against Greengenes database. The α and β diversity and the Kruskal Wallis test were performed by QIIME software. Results: The T test on good's coverage index revealed that the qualitative composition of the gut microbiota between the T0 and T2 conditions resulted significantly different. Box plot of Shannon and Chao I indices revealed an increase in the median index values at the time point T1, which means an increase in the OTU total number at T1. This indicates an increase of the microbiota wellness at this time point. Post hoc analysis at phylum taxonomic level, revealed that Firmicutes relative abundance in the condition T0 versus T1 resulted significantly different, with a decrease of Firmicutes at T1. Indeed, at family taxonomic level the post hoc analysis revealed that Clostridiaceae relative abundance in the condition T0 versus T1, and also in T1 versus T2, differed significantly, with a T1 median value higher than the T0 and T2 values. At genus level, the T test confirms the variability in the two conditions (T0 and T2), with significantly differences for Actinomyces, Anaerostipes, Bacteroides, Bulleidia, Corynebacterium, Dialister, Enterobacteriaceae, Erysipelotrichaceae, Finegoldia, Granulicatella, Lactobacillaceae, Peptoniphilus, Phascolarctobacterium, Roseburia, Serratia, Veillonellaceae, Veillonella_dispar, belonging to Firmicutes, Bacteroidetes and Proteobacteria phyla. Conclusions: Treatment with ECN leads to an improvement of the qualitative gut microbiota composition in UC patients. These effects are stronger at the end of treatment, with a stable variability between the genera after 1 month of treatment.